THE FEATURES OF FORMATION AND THE CURRENT STATE OF HIGHER EDUCATIONAL INSTITUTIONS LEADERSHIP’S PROFESSIONAL TRAINING SYSTEM IN UKRAINE - Gromova S.O. (Pressing Problems of Public Administration, 2015)
The condition of higher educational system leadership’s training in Ukraine is analyzed.The necessity of the construction and functioning the mechanism of higher educationalinstitutions leadership’s professional training public administration system is grounded. The stateof of higher educational system leadership’s training in Ukraine at the basic of the NationalAcademy of Public Administration attached to the office the President of Ukraine is analyzed.